The Effectiveness of Combined Benson Therapy and Warm Water Bath Therapy in Reducing High Blood Pressure in the Hamlet of Aik Ngempok, Pengadangan Village: Efektifitas Kombinasi Terapi Benson Dengan Terapi Rendam Air Hangat Dalam Penurunan Tekanan Darah Tinggi Di Dusun Aik Ngempok Desa Pengadangan - Muhamad Wahyu Ihwandia; Anatun Aupia (PT. Sentra Ilmiah Teknologi Mandiri, 2026)
Hypertension is a condition characterized by an abnormal increase in blood pressure, indicated by systolic and diastolic blood pressure values exceeding 140/90 mmHg. Treatment for patients with hypertension can be carried out through two approaches: pharmacological and non-pharmacological therapies. Pharmacological treatment is commonly administered through the use of medications, such as diuretics. Meanwhile, non-pharmacological treatment can be implemented through methods such as combination of Benson relaxation therapy and warm water immersion therapy. This study aims to evaluate the effectiveness of combining Benson relaxation therapy and warm water immersion therapy in reducing blood pressure among patients with hypertension. This study employed a qualitative descriptive design using a case study approach in the nursing process, which included assessment, diagnosis, intervention/planning, implementation, and evaluation. Based on the evaluation conducted by the researcher on Mrs. N, the final assessment showed that the client's blood pressure had decreased after receiving Benson relaxation therapy and warm water immersion therapy for three consecutive days. Nursing care provided to a patient with hypertension, including Benson relaxation therapy for 3 × 24 hours, was found to reduce the patient's blood pressure and improve quality of life. Based on these findings, it can be concluded that the application of combining the Benson relaxation andwarm water immersion therapy is effective in lowering blood pressure.